Hearing Performance and Soft-Tissue Outcomes of Minimally Invasive Ponto Surgery and Local Anesthesia in Children with Unilateral Craniofacial Malformation - Andrea Caruso Leone; Arthur Menino Castilho; Fabiana Danieli; Daniela Bortoloti Calil; Katia de Almeida (International Archives of Otorhinolaryngology)
Introduction Minimally invasive Ponto surgery (MIPS) enables the installation of percutaneous bone-anchored hearing implants (BAHIs) with a drill guide through a hole punch incision. Despite being well established for adults, there is a lack of studies in the literature regarding its use in pediatric patients.